The Life of Deli Tobacco Plantation's Workers in East Sumatera, 1880-1930 - Ririn Darini; Dyah Ayu Anggraeni (IHiS (Indonesian Historical Studies), 2021)
This paper aims to reveal the life of Deli tobacco plantation workers in East Sumatra during the period 1880-1930. The problem was focused on the policies issued by the colonial government on labor and its implementation, and its consequences for the lives of the plantation workers. This study applies a historical method which includes four stages, namely heuristics, criticism, interpretation, and historiography. The results showed that through a variety of policies that apply in plantations cause daily laborers were very tied to plantation life. They will receive physical sanctions if they violate the rules. The living facilities on the plantations were initially very limited, although later efforts were made to improve the company. Meanwhile the entertainment facilities that they get on plantations such as prostitution, gambling and madat actually make their lives even more difficult.